About the Spiritual Element in Lengger Banyumas - Bugov, Dobrin Tsvetanov (Harmonia: Journal of Arts Research and Education, 2024)
This research aims to trace the relevancy of the spiritual element in the rural dance art form lengger Banyumas. The art originated in Banyumas, Central Java, Indonesia, as a dance in agricultural ceremonies to worship the Goddess of Fertility, Dewi Sri, but it developed and assimilated new functions, such as entertainment, in terms of performance. Despite that, the spiritual connection of the dance with the Divine remained, and it can be seen in the relationship between the dancer, God, and nature which remained unchanged over time. This is shown through a thick description of the process of becoming a lengger dancer, the existence of holy places, as well as the use of offerings in lengger performances. The research method of this study is a critical historical, based on one and half years of research in Banyumas. The techniques used are participant observation, in-depth and semi-structured interviews, as well as visual data (photos and videos). In terms of interviews, the research involved about 13 informants, all of which related to lengger in some way. Results show that spirituality is still very much relevant in the world of lengger and is an inseparable part of the performance and the life of dancers despite being subject to changes. The presence of the spiritual element in lengger nowadays speaks about how important the connection between the Divine is in Java, Indonesia.